Analysis of The Added Value of Gastric Healthy Yellow Honey and Deternimation of Cost of Goods Produced With Full Costing Method as a Basis For Determaning Selling Prices - Nirmalasari, Suci; Miftah, Himmatul; Yoesdiarti, Arti (JURNAL AGRIBISAINS, 2025)
The study's goals are to(1) determine the value of gastric healthy yellow honey as a raw material for herbal medicine in CV Herbattaubah,(2) determine the cost of goods produced using a full costing system on CV Herbattaubah, and(3) compare the company's method with the full costing method in calculating the cost of goods produced, which gives the basis for determining the selling price of products using cost plus pricing. Both primary and secondary sources of information were poured into this investigation. The organizations that participate in the survey are selected using a purposive sampling approach. The respondents might include CEOs, production managers, and financial managers, among others. Quantitative analysis is performed utilizing the Hayami technique using analytical equipment with added value. Gastric Healthy Yellow Honey was produced from honey with an added value of Rp.77.198,59/kg of raw honey, according to the findings. This study determined that CV Herbattaubah's Gastric Healthy Yellow Honey could generate up to 2,400 bottles every cycle, allowing us to calculate a total production cost per bottle of Rp. 75,543/bottle. With a Rp.19,456,-profit margin each bottle. Using the company's method to determine the selling price (Rp.95,000) and the cost plus pricing method (Rp.105,760) result in a different difference of Rp.44.543.